Keadilan Restorative Justice Melalui Kebijakan Diversi Dalam Sistem Peradilan Anak - Edi Saputra Hasibuan (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
The position of the rights and obligations of everyone in court is the same, but as a special relationship in the criminal justice system, children must receive different treatment, considering that children are an inseparable part of human survival and the sustainability of the nation and state. Law no. 11 of 2012 concerning the juvenile justice system emerged as a form of intention to create child-friendly courts, even looking further at the most basic substance of this rule, namely promoting the principles of restorative justice with a view to finding a settlement of cases without having to go through a trial. However, in practice there are still child cases that continue to take legal action through the courts. These problems will then be discussed, looking at the policies and realities as well as benchmarks about what kind of cases can be resolved in every process of resolving child cases in court.